Capturing Chromosome Conformation Methods and Protocols - Bodega, Beatrice; Lanzuolo, Chiara; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Humana, 2021)
This detailed book collects methods based on the evolution of the chromosome conformation capture (3C) technique and other complementary approaches to dissect chromatin conformation with an emphasis on dissection of nuclear compartmentalization and visualization in imaging. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Capturing Chromosome Conformation: Methods and Protocols serves as an ideal guide for researchers working to further understand 3D genome organization.
Capturing Chromosome Conformation -- The Chromosome Conformation Capture (3C) in Drosophila melanogaster -- 4C-Seq: Interrogating Chromatin Looping with Circular Chromosome Conformation Capture -- Analysis, Modeling, and Visualization of Chromosome Conformation Capture Experiments -- Targeted DNase Hi-C -- C-HiC: A High Resolution Method for Unbiased Chromatin Conformation Capture Targeting Small Locus -- Computational Analysis of Hi-C Data -- Profiling Chromatin Landscape at High Resolution and Throughput with 2C-ChIP -- Single-Cell DamID to Capture Contacts between DNA and the Nuclear Lamina in Individual Mammalian Cells -- Formaldehyde-Mediated Snapshot of Nuclear Architecture -- Visualization of Chromatin Dynamics by Live Cell Microscopy Using CRISPR/Cas9 Gene Editing and ANCHOR Labeling -- Preparing Map of Chromosome Territories Distribution Frequency -- Higher-Order Chromatin Organization Using 3D DNA Fluorescent In Situ Hybridization -- 3D Immuno-DNA Fluorescence In Situ Hybridization (FISH) for Detection of HIV-1 and Cellular Genes in Primary CD4+ T Cells -- Visualization of Nuclear and Cytoplasmic Long Noncoding RNAs at Single-Cell Level by RNA-FISH -- 3D COMBO chrRNA-DNA-Immuno FISH -- An Algorithm for the Analysis of the 3D Spatial Organization of the Genome.
Keywords: Biology$1 (BTechnique.s; Cell biology; Genetics; Biological Techniques; Cell Biology; Genetics and Genomics